Enlightening Minds through Research, Nurturing Hearts through Practice ——A Study on the Improvement Paths and Practical Strategies of County Primary School Principals’ Study Tour Leadership ——A Case Study on the Construction of a Three-Tier Study Tour System under the "Seven-Character Education" Culture of Bin County No.7 Primary School - Hongmei He; Qiqi Song (Education Research on Study Tours and Practice, 2026)
Guided by the fundamental task of moral education and the strategic orientation of practical education, study tours have been upgraded from extracurricular activities to a mandatory educational carrier, with principals’ study tour leadership becoming the core determinant of educational quality. Taking Bin County No.7 Primary School as the research sample and its "Seven-Character Educational Culture" as the core, this paper targets three key competencies: overall planning, organizational management and resource integration. It constructs a three-stage progressive study tour system of "Red Culture for Soul Cultivation, Military Experience for Aspiration Forging, and Science & Technology for Intelligence Enlightenment", and explores hierarchical implementation paths for lower, middle and senior grades. The study develops a replicable and promotable model for improving principals’ study tour leadership in county primary schools, providing practical experience and theoretical reference for the high-quality development of study tour education in primary and secondary schools of Heilongjiang Province.